2020
DOI: 10.3390/sym12050816
|View full text |Cite
|
Sign up to set email alerts
|

Switching Perfect Control Algorithm

Abstract: The application of the switching control framework to the perfect control algorithm is presented in this paper. Employing the nonunique matrix inverses, the different closed-loop properties are obtained and further enhanced with possible switching methodology implementation. Simulation examples performed in the MATLAB/Simulink environment clearly show that the new framework can lead to benefits in terms of the control energy, speed, and robustness of the perfect control law. The possibility of transferring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Having dynamic or static properties of the system, it is possible not only to precisely determine the control parameters for the assumed operating point but also to obtain highly positive results of the complex plant operations. This is confirmed, for instance, by the multivariable state-space perfect control procedure, which allows us to receive a reference value for the single-delayed object just after one simulation step time [1,2]. Thus, the proper modeling and identification often provide the efficient control plants.…”
Section: Introductionmentioning
confidence: 92%
“…Having dynamic or static properties of the system, it is possible not only to precisely determine the control parameters for the assumed operating point but also to obtain highly positive results of the complex plant operations. This is confirmed, for instance, by the multivariable state-space perfect control procedure, which allows us to receive a reference value for the single-delayed object just after one simulation step time [1,2]. Thus, the proper modeling and identification often provide the efficient control plants.…”
Section: Introductionmentioning
confidence: 92%
“…Nevertheless, studies have shown that, in non-square plants, it is possible to reduce the said energy injection even up to 80% in the context of an appropriate choice of so-called degrees of freedom emerging in a properly selected inverse [ 18 ]. Moreover, it is possible to select good control parameters for the selected operating point while maintaining low energy consumption and high accuracy [ 9 , 15 , 18 , 19 , 20 , 21 , 22 ]. However, the reduction mentioned here, even at the level of ten percent, may not be sufficient for some systems.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse model control (IMC) has widely been investigated over the past decades due to its application in many scientific and engineering fields [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25]. The unique behaviors of the discussed technique such as robustness, maximumspeed or minimum-energy properties make it attractive in many practical implementations [1], [9], [12], [23], [26], [27], [28].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the multivariable nonsquare right-invertible plants, i.e. systems with greater number of input than output variables, can also be subjected by such noise-free control law [3]. In such a case, through the application of nonunique parameter/polynomial right inverses, we can redefine the special properties of the closed-loop state-feedback plant [1], [9], [26].…”
Section: Introductionmentioning
confidence: 99%